Legal Policy on Criminal Sanctions for Environmental Offenses at The En-vironmental Agency of Prabumulih City - Rishi Suparianto (LEGAL BRIEF, 2026)
This study examines legal policies regarding criminal sanctions for environmental crimes, focusing on their implementation at the Prabumulih City Environmental Agency. The problem arises because Law Number 32 of 2009 places criminal sanctions as the ultimum remedium, while local law enforcement practices still predominantly utilize administrative and civil sanctions. The study was conducted using a normative juridical approach, analyzed through literature and legal document studies, and supplemented by empirical observations of monitoring and enforcement practices in Prabumulih City. The results indicate that environmental criminal sanctions are not applied optimally, inter-agency coordination remains limited, and public participation in environmental monitoring is low, resulting in the ineffective prevention and prosecution of environmental violations under criminal law. The critical analysis emphasizes the need to reposition criminal sanctions as the primary instrument, increase the capacity of the Environmental Agency, and strengthen synergy between the state and the community. These findings are expected to inform policymakers and law enforcement officials to strengthen environmental protection at the regional and national levels